Environmental impact of ASEAN-China free trade agreement: A case of Indonesia palm oil industry 2005-2010. Issue 1 (April 2021) - Natalia, J; Mursitama, T N; Noerlina,
Abstract: This research focused on the impact of the ASEAN-China Free Trade Agreement (ACFTA) on the environment of the Indonesian palm oil industry. The theory used in this research was trade liberalization impact with scale effect, composition effect, and technique effect as the variable to seek the environmental impact of trade liberalization. The method of this research used a qualitative approach and explanatory data analysis technique. This research indicates that ACFTA has a positive impact on the member states' economy. However, on the other hand, ACFTA has a negative impact on the environment because of deforestation and increased carbon emissions. Deforestation and increased carbon emission are caused by the expansion of palm land area, which is encouraged by the escalation in demand for palm oil products in the free trade area.